Congenital anomaly epidemiological correlates of Δ8THC across USA 2003–16: panel regression and causal inferential study. Issue 1 (17th May 2022) - Reece, Albert Stuart; Hulse, Gary Kenneth
Abstract: Δ8-Tetrahydrocannabinol (Δ8THC) is marketed in many US states as 'legal weed'. Concerns exist relating to class-wide genotoxic cannabinoid effects. We conducted an epidemiological investigation of Δ8THC-related genotoxicity expressed as 57 congenital anomaly (CA) rates (CARs) in the USA. CARs were taken from the Centers for Disease Control, Atlanta, Georgia. Drug exposure data were taken from the National Survey of Drug Use and Health, with a response rate of 74.1%. Ethnicity and income data were taken from the US Census Bureau. National cannabinoid exposure was taken from Drug Enforcement Agency publications and multiplied by state cannabis use data to derive state-based estimates of Δ8THC exposure. At bivariate continuous analysis, Δ8THC was associated with 23 CAs on raw CA rates, 33 CARs after correction for early termination for anomaly estimates and 41 on a categorical analysis comparing the highest and lowest exposure quintiles. At inverse probability weighted multivariable additive and interactive models lagged to 0, 2 and 4 years, Δ8THC was linked with 39, 8, 4 and 9 CAs. Chromosomal, cardiovascular, gastrointestinal, genitourinary, limb, central nervous system (CNS) and face systems were particularly affected. The minimum E -values ranged to infinity. Both the number of anomalies implicated and the effect sizes demonstrated were much greater for Δ8THC than for tobacco and alcohol combined. Δ8THC appears epidemiologically to be more strongly associated with many CAs than for tobacco and alcohol and is consistent with a cannabinoid class genotoxic/epigenotoxic effect. Quantitative causality criteria were fulfilled, and causal relationships either for Δ8THC or for cannabinoid/s, for which it is a surrogate marker, may be in operation.